2021
DOI: 10.1038/s41586-021-04015-y
|View full text |Cite
|
Sign up to set email alerts
|

In-orbit demonstration of an iodine electric propulsion system

Abstract: Propulsion is a critical subsystem of many spacecraft1–4. For efficient propellant usage, electric propulsion systems based on the electrostatic acceleration of ions formed during electron impact ionization of a gas are particularly attractive5,6. At present, xenon is used almost exclusively as an ionizable propellant for space propulsion2–5. However, xenon is rare, it must be stored under high pressure and commercial production is expensive7–9. Here we demonstrate a propulsion system that uses iodine propella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 44 publications
0
55
0
1
Order By: Relevance
“…无机化学作为化学类本科生学习的第一门专业基础课,课程内容广泛,是分析化学、物理化学 等多门专业课程的基础,因此无机化学课程的重要性不言而喻 [2] 。我校化学专业于2020年入选教育 部"双万计划"国家级一流本科专业建设点,结合国家一流专业的建设要求,积极探索新的教学理 念和教学方法,成为本课程教学改革的核心内容,也是建设无机化学一流课程、支撑化学国家一流 本科专业建设的重要引擎。在教学过程中,紧密契合我校培养"新时代知农爱农新型人才"的特色 和目标,以立德树人为中心任务,实施科研反哺教学。这能够让学生认识到自己所学的知识有用武 之地,并增强学生对专业的认同感,进一步激发学生的学习兴趣、科研兴趣;不仅为学生后续专业 课的学习打好基础,还为其考研深造起到重要引领,由此可见在教学过程中探索科研反哺教学的重 要性。 诸多高校针对化学专业实施科研反哺教学进行了探索 [3,4] ,但在实际的教学实践中仍存在以下问 题:(1) 科研反哺教学的资源有限:化学是实验性强的学科,因此学生动手做实验是实现科研反哺教 学的最佳方式,但目前很多地方高校由于科研实力弱、科研设备设施不足等资源限制导致科研反哺 教学效果差 [5] 。(2) 学生不能将科研内容及课堂知识相联系:目前学生在大学二年级甚至一年级就可 能进入实验室,但是与科研相关的专业课程大多设置在大学二年级及以后,因此很多学生尤其是低 年级的学生进入实验室后,不能真正地将自己在课堂上所学的知识应用到实验过程中,这对于学生 后续科研道路的发展是不利的。因此,并不是学生进了实验室,就是我们做好了科研反哺教学。 针对科研反哺教学中存在的问题,武汉大学蔡苹等 [6] 通过分析无机化学基本知识与相关的科研 文献,提出了基础知识与前沿的协同作用;北京航空航天大学张东凤等 [7] 以纳米材料的合成中涉及 到的无机化学基础知识为例,阐述了基础知识与科学前沿课题之间的密切联系。上述研究虽然从表 面上解决了"科研反哺教学资源有限"问题,但所引入的内容学习难度较大,学生参与度低。因此, 为了增加科研反哺教学过程中学生的参与度,更好地将学科前沿内容融入课堂,提高科研反哺教学 的教学效果,本文结合我校无机化学课程教学实践,探索建立了立足教材、追踪前沿的"三步法" 科研反哺教学方法。 氧化还原反应 氧还原反应(ORR)是燃料电池等能量转换器 件中的重要催化反应 非贵金属(Fe-N-C)用于燃料电池的阴极氧还原电催化剂 [8] 催化剂 催化过程的基本原理 原位观察到催化过程 [9] 化学热力学 偏二甲肼和四氧化二氮反应放出大量的热 作为火箭推进剂 碘加热时直接转化为气体,可以用作卫星推进剂 [10] 配合物的性质 配合物可以作为催化反应的催化剂 N,N,N三齿配体修饰的新型锰基配合物具有与贵金属光活性分子类似的 荧光及光催化性质 [11] 氢键 简介分子动力学模拟 理论模拟与实验观测相结合解释冰面为什么滑 [12] 化学反应速率 一般的化学反应速率测定的方法 水合电子及水合电子前体寿命的探测 [13] 沉淀的生成 沉淀生成原理用于纳米材料的合成 MOF合成中成核过程的具体细节研究 [14] a 科学前沿内容紧跟学科发展,内容动态更新 下面以"沉淀的生成"这一节的课程内容设计为例,阐述立足教材、追踪前沿的"三步法"科 研反哺教学方案的具体实施方法及其注意事项。 2.…”
Section: 够提前进入科研实验室,学生的创新实践能力得到提高;另一方面将最新科研成果转化为教学内容, 既能使学生具有扎实的理论基础,...unclassified
“…无机化学作为化学类本科生学习的第一门专业基础课,课程内容广泛,是分析化学、物理化学 等多门专业课程的基础,因此无机化学课程的重要性不言而喻 [2] 。我校化学专业于2020年入选教育 部"双万计划"国家级一流本科专业建设点,结合国家一流专业的建设要求,积极探索新的教学理 念和教学方法,成为本课程教学改革的核心内容,也是建设无机化学一流课程、支撑化学国家一流 本科专业建设的重要引擎。在教学过程中,紧密契合我校培养"新时代知农爱农新型人才"的特色 和目标,以立德树人为中心任务,实施科研反哺教学。这能够让学生认识到自己所学的知识有用武 之地,并增强学生对专业的认同感,进一步激发学生的学习兴趣、科研兴趣;不仅为学生后续专业 课的学习打好基础,还为其考研深造起到重要引领,由此可见在教学过程中探索科研反哺教学的重 要性。 诸多高校针对化学专业实施科研反哺教学进行了探索 [3,4] ,但在实际的教学实践中仍存在以下问 题:(1) 科研反哺教学的资源有限:化学是实验性强的学科,因此学生动手做实验是实现科研反哺教 学的最佳方式,但目前很多地方高校由于科研实力弱、科研设备设施不足等资源限制导致科研反哺 教学效果差 [5] 。(2) 学生不能将科研内容及课堂知识相联系:目前学生在大学二年级甚至一年级就可 能进入实验室,但是与科研相关的专业课程大多设置在大学二年级及以后,因此很多学生尤其是低 年级的学生进入实验室后,不能真正地将自己在课堂上所学的知识应用到实验过程中,这对于学生 后续科研道路的发展是不利的。因此,并不是学生进了实验室,就是我们做好了科研反哺教学。 针对科研反哺教学中存在的问题,武汉大学蔡苹等 [6] 通过分析无机化学基本知识与相关的科研 文献,提出了基础知识与前沿的协同作用;北京航空航天大学张东凤等 [7] 以纳米材料的合成中涉及 到的无机化学基础知识为例,阐述了基础知识与科学前沿课题之间的密切联系。上述研究虽然从表 面上解决了"科研反哺教学资源有限"问题,但所引入的内容学习难度较大,学生参与度低。因此, 为了增加科研反哺教学过程中学生的参与度,更好地将学科前沿内容融入课堂,提高科研反哺教学 的教学效果,本文结合我校无机化学课程教学实践,探索建立了立足教材、追踪前沿的"三步法" 科研反哺教学方法。 氧化还原反应 氧还原反应(ORR)是燃料电池等能量转换器 件中的重要催化反应 非贵金属(Fe-N-C)用于燃料电池的阴极氧还原电催化剂 [8] 催化剂 催化过程的基本原理 原位观察到催化过程 [9] 化学热力学 偏二甲肼和四氧化二氮反应放出大量的热 作为火箭推进剂 碘加热时直接转化为气体,可以用作卫星推进剂 [10] 配合物的性质 配合物可以作为催化反应的催化剂 N,N,N三齿配体修饰的新型锰基配合物具有与贵金属光活性分子类似的 荧光及光催化性质 [11] 氢键 简介分子动力学模拟 理论模拟与实验观测相结合解释冰面为什么滑 [12] 化学反应速率 一般的化学反应速率测定的方法 水合电子及水合电子前体寿命的探测 [13] 沉淀的生成 沉淀生成原理用于纳米材料的合成 MOF合成中成核过程的具体细节研究 [14] a 科学前沿内容紧跟学科发展,内容动态更新 下面以"沉淀的生成"这一节的课程内容设计为例,阐述立足教材、追踪前沿的"三步法"科 研反哺教学方案的具体实施方法及其注意事项。 2.…”
Section: 够提前进入科研实验室,学生的创新实践能力得到提高;另一方面将最新科研成果转化为教学内容, 既能使学生具有扎实的理论基础,...unclassified
“…Furthermore, when operating an iodine-fed EP system, different parts of the satellite are exposed to different iodine partial pressures. Typical partial pressures inside the propellant feed system will be 2 to 6 kPa [5] and inside of the thruster about 1 to 2.5 Pa [19]. Outside the thruster, typical iodine partial pressure inside the plume will be about 1e-3 Pa and will decrease with increasing distance from the satellite down to high vacuum conditions.…”
Section: How To Mimic Space Environment Of Satellites With Iodine-fed...mentioning
confidence: 99%
“…Iodine is a possible alternative, since it is also a heavy atom, but much cheaper than xenon. In addition, no pressurized storage tanks are required for iodine, which further reduces the total costs and enables an easier implementation into small satellites [5,6]. Recently, Rafalskyi et al [5] demonstrated the first satellite with an iodine-fed propulsion system in space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the μCAT firing, a solid converts into plasma, which can be further accelerated by electromagnetic fields. Despite the other miniature electrical thrusters with a solid propellant (such as an iodine thruster) ( 7 ), μCATs do not use toxic propellants, and they do not have a warm-up time; i.e., they can be ignited instantly after providing the respective control signal. The μCATs’ performance has been successfully demonstrated in flight tests during Ballistic ReInforced Communication Satellite (BRICSat), The CubeSat Astronomy by NASA and Yonsei using the Virtual Telescope ALignment-eXperiment (CANYVAL-X), and Ballistic ReInforced Communication Satellite–Propulsive Test Unit (BRICSat-P) missions ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%